A modified optical fiber and laser therapeutic device thereof

By adopting a modified optical fiber with a three-layer composite structure, using light curing technology of epoxy resin and acrylic materials, and combining the addition of rare earths and fatty acids, the problems of low transmission efficiency and electrostatic interference of existing optical fibers are solved, and efficient optical fiber transmission is achieved. Signal transmission and electrostatic shielding.

CN114966948BActive Publication Date: 2025-01-21GUILIN WOODPECKER MEDICAL INSTR CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202210379702.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-04-12
Publication Date
2025-01-21
Estimated Expiration
2042-04-12

AI Technical Summary

Technical Problem

The existing optical fiber transmission efficiency is low, mainly due to the electromagnetic interference caused by excessive total reflections and electrostatic discharge, which affects the coherence and intensity of the laser.

Method used

A modified optical fiber with a three-layer composite structure, including core, cladding and coating layer. The coating layer is composed of epoxy resin compounds and acrylate compounds and is prepared by light curing. Rare earth and fatty acid compounds are added to Improve transmission efficiency and electrostatic shielding effect.

Benefits of technology

It significantly improves the transmission efficiency of optical fiber, reduces the light intensity attenuation rate to 0.9%, effectively shields electrostatic interference, and enhances the power and application range of the laser therapy instrument.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114966948B_ABST
    Figure CN114966948B_ABST
Patent Text Reader

Abstract

The present invention relates to the field of optical fibers, and specifically to a modified optical fiber and a laser therapy device thereof. The modified optical fiber provided by the present invention comprises, from the inside to the outside, a core, a cladding and a coating layer, and the coating layer is prepared by curing a photocurable material through light irradiation, and is characterized in that the photocurable material comprises an epoxy resin compound and an acrylate compound. The modified optical fiber provided by the present invention has high transmission efficiency and a short curing time required during preparation. Experimental results show that the light intensity attenuation rate of the modified optical fiber of the present invention can be reduced to as low as 0.9%, and the light transmission efficiency is greatly improved compared with ordinary optical fibers. The laser therapy device provided by the present invention comprises the above-mentioned modified optical fiber. Due to the low light intensity attenuation rate of the above-mentioned modified optical fiber, the laser therapy device has a higher power and thus has a larger range of applications.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of optical fibers, in particular to a modified optical fiber and a laser therapeutic device thereof. Background Art

[0002] Optical fiber is the full name of optical fiber, which can be used as a light transmission tool. Due to the loss of various media and other reasons, the existing optical fiber generally has a light transmission efficiency of only 90% or even lower.

[0003] Existing laser products, such as laser therapy devices, generally transmit lasers through optical fibers. For step-refractive optical fibers commonly used in laser products, the plane passing through the central axis of the optical fiber is called the meridian plane, and the light within the meridian plane is called the meridian ray. According to the law of reflection of light, when light is reflected at the internal interface of the optical fiber, the normal of the interface is the radius of the fiber core. Therefore, the incident light, reflected light, and normal of the interface of the meridian ray are all within the meridian plane. This is the characteristic of meridional ray propagation. In actual use, optical fibers are often in a bent state, or due to the inconsistency of the refractive index of the optical fiber material, the optical path length, numerical aperture and other parameters will change. For example Figure 1 As shown, Figure 1 is the propagation diagram of light in the optical fiber; when the meridian light propagates in the optical fiber, the calculation formulas for the optical path length L' and the total reflection number q per unit length are L'=1 / cosθ=1 / sinψ and q=tanθ / 2a=1 / (2a×tanψ), respectively, where θ is the incident angle of the light deviating from the meridian light, and ψ is the refraction angle between the optical fiber material and the sheath material. One of the important reasons for the low transmission efficiency of existing optical fibers is that the total reflection number q is too high, that is, the refraction angle between the optical fiber material and the sheath material is too small.

[0004] In addition, electrostatic discharge (ESD) is also one of the factors that affect the performance of optical fiber. It is a very fast process, with a rise time of less than one billionth of a second, or even less than hundreds of trillionths of a second. This process can generate tens of kilovolts per meter or even stronger electromagnetic pulses. Static electricity can absorb dust, change line impedance, and affect the function and life of the product. Existing optical fibers are not well shielded from electromagnetic radiation and are susceptible to electromagnetic interference, which leads to a decrease in the coherence of the laser and thus a decrease in the laser intensity.

[0005] The transmission efficiency of laser from the generator to the end user is limited by the above factors, which limits the application of laser products. Therefore, it is necessary to design an optical fiber that can reduce the loss of laser during transmission and effectively shield static electricity, so as to improve the transmission efficiency of optical fiber. Summary of the invention

[0006] In view of this, the technical problem to be solved by the present invention is to provide a modified optical fiber and a laser therapy device thereof. The modified optical fiber provided by the present invention has high transmission efficiency and short curing time required during preparation.

[0007] The present invention provides a modified optical fiber, which comprises a core, a cladding and a coating layer from the inside to the outside, wherein the coating layer is prepared by curing a photocurable material through light irradiation, and is characterized in that the photocurable material comprises an epoxy resin compound and an acrylic compound.

[0008] Specifically, the modified optical fiber of the present invention has a three-layer composite structure, which includes a core, a cladding and a coating layer from the inside to the outside.

[0009] The fiber core of the present invention is the central area of ​​the optical fiber, through which most of the light signals pass. It is drawn from glass. Glass of different compositions has different refractive indices, and the prepared optical fibers also have different signal losses. In one embodiment, the main component of the fiber core is quartz glass, multi-component glass or polymer glass. In one embodiment, the main components of the fiber core include: 20-54wt% SiO2, 10-16wt% Na2O, 5-9wt% K2O, 10-16wt% CaO, 5-9wt% BaO, 10-16wt% ZnO, 5-9wt% B2O3 and 1-5wt% GeO2.

[0010] The cladding of the present invention is a layer of glass coated on the surface of the core, and its refractive index is lower than that of the core, so that the light is totally reflected at the interface between the core and the cladding, thereby transmitting the optical signal, and also protecting the core. In one embodiment, the main component of the cladding is quartz glass, multi-component glass or polymer glass. In one embodiment, the main components of the cladding include: 25-55wt% SiO2, 10-16wt% Na2O, 5-9wt% K2O, 10-16wt% CaO, 5-9wt% BaO, 10-16wt% ZnO and 5-9wt% B2O3.

[0011] The coating layer of the present invention is prepared by light curing of a photocurable material, and the photocurable material includes an epoxy resin compound and an acrylate compound. The coating layer can protect the optical fiber from damage and effectively prevent signal attenuation; the acrylate compound can act as a prepolymer and a photoinitiator during the light curing process. In one embodiment, the epoxy resin compound is one or more of bisphenol A epoxy resin or novolac epoxy resin. In one embodiment, the acrylate compound is one or more of methyl acrylate, ethyl acrylate, 2-methyl methacrylate or 2-ethyl methacrylate. In one embodiment, the mass ratio of the epoxy resin compound to the acrylate compound is 1:1 to 3. In one embodiment, the mass ratio of the epoxy resin compound to the acrylate compound is 1:2.

[0012] The present invention can enhance the curing effect by adding a photoinitiator to the photocurable material. In one embodiment, the photoinitiator includes one or more of a free radical photoinitiator or a cationic photoinitiator; in one embodiment, the free radical photoinitiator includes one or more of benzil, α-hydroxyalkyl phenone or acylphosphine oxide; in one embodiment, the cationic photoinitiator includes one or more of a diazonium salt, a diaryl iodonium salt, a triaryl sulfonium salt, an alkyl sulfonium salt, an iron aromatic salt, a sulfonyloxy ketone or a triaryl siloxane; in one embodiment, the amount of the photoinitiator added to the photocurable material is 0.1 to 5 wt%.

[0013] The present invention further reduces the time of photocuring when preparing the coating layer by adding fatty acid compounds to the photocurable material, and the transmission efficiency of the optical fiber obtained does not decrease. In one embodiment, the photocurable material includes epoxy resin compounds, acrylate compounds and fatty acid compounds; in one embodiment, the fatty acid compounds are one or more of octanoic acid, caprylic acid or linoleic acid. In one embodiment, the amount of the fatty acid compound added to the photocurable material is 0.1 to 5wt%. In one embodiment, the amount of the fatty acid compound added to the photocurable material is 2wt%.

[0014] The present invention adds rare earth to the photocurable material so that the prepared coating layer is doped with rare earth, thereby increasing the refraction angle of laser transmission and further enhancing the optical fiber transmission efficiency. In one embodiment, the photocurable material includes epoxy resin compounds, acrylate compounds and rare earth. In one embodiment, the photocurable material includes epoxy resin compounds, acrylate compounds, fatty acid compounds and rare earth. In one embodiment, the rare earth is one or more of erbium oxide, samarium oxide, and cerium oxide. In one embodiment, the rare earth is added to the photocurable material in an amount of 0.1 to 5wt%. In one embodiment, the rare earth is added to the photocurable material in an amount of 1wt%.

[0015] In the present invention, the modified optical fiber also includes a plastic shell reinforced by a metal product coated on the coating layer. The plastic shell reinforced by the metal product can improve the electrostatic shielding effect of the optical fiber and avoid the interference of the external electromagnetic environment on the laser transmitter. In one embodiment, the metal product is a mesh metal or a coil metal. In one embodiment, the metal is iron, chromium, nickel, copper, aluminum, gold, silver, platinum or an alloy thereof. In one embodiment, the plastic is ABS plastic, polycarbonate plastic or polyester plastic.

[0016] The present invention also provides a laser therapeutic apparatus, comprising the modified optical fiber.

[0017] The modified optical fiber provided by the present invention includes a core, a cladding and a coating layer from the inside to the outside, and the coating layer is prepared by curing a photocurable material through light exposure, and is characterized in that the photocurable material includes epoxy resin compounds and acrylic compounds. The modified optical fiber provided by the present invention has high transmission efficiency and short curing time required for preparation; the present invention further shortens the light curing time by adding fatty acid compounds to the photocurable material; by adding rare earth to the photocurable material, the coating layer is doped with rare earth, which further improves the transmission efficiency of the optical fiber; the electrostatic shielding effect of the optical fiber is improved by coating the coating layer with a plastic shell reinforced by metal products. Experimental results show that the light intensity attenuation rate of the modified optical fiber of the present invention can be reduced to 0.9% at the lowest, and the light transmission efficiency is greatly improved compared with ordinary optical fibers. The laser therapeutic device provided by the present invention includes the above-mentioned modified optical fiber; due to the high light transmission efficiency of the above-mentioned modified optical fiber, the laser therapeutic device has a higher power and thus has a larger application range. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 is the propagation diagram of light in optical fiber;

[0019] Figure 2 It is a cross-sectional structural diagram of an optical fiber without a shell on the coating layer;

[0020] Figure 3 It is a cross-sectional structural diagram of an optical fiber with a shell coated on the coating layer. DETAILED DESCRIPTION

[0021] The present invention discloses a modified optical fiber and a laser therapy device thereof. Those skilled in the art can refer to the content of this article and appropriately improve the process parameters to achieve it. It is particularly important to point out that all similar substitutions and modifications are obvious to those skilled in the art, and they are all considered to be included in the present invention. The method and application of the present invention have been described through preferred embodiments, and relevant personnel can obviously modify or appropriately change and combine the method and application of this article without departing from the content, spirit and scope of the present invention to implement and apply the technology of the present invention.

[0022] The present invention will be further described below in conjunction with embodiments:

[0023] The chemical composition of the fiber core and cladding of the present invention is shown in Table 1:

[0024] Table 1

[0025]

[0026] Comparative Example 1

[0027] According to the chemical composition of the fiber core described in Table 1, appropriate amounts of raw materials were weighed, mixed evenly and placed in a crucible, the crucible was placed in a muffle furnace, heated to 1600°C in a N2 atmosphere and melted for 2 hours, then cooled to 1400°C with the furnace to obtain a core glass liquid, the core glass liquid was poured on a mold to solidify into glass, then annealed at 320°C for 300 minutes in a muffle furnace, naturally cooled to room temperature after annealing, and finally taken out and polished to obtain a core glass rod.

[0028] According to the chemical composition of the cladding in Table 1, appropriate amounts of raw materials were weighed, mixed evenly and placed in a crucible, the crucible was placed in a muffle furnace, heated to 1600° C. for melting for 2 h in a N2 atmosphere, and then cooled to 1400° C. with the furnace to obtain cladding glass liquid, which was poured on a tube sleeve mold to solidify into glass, then annealed at 320° C. for 300 min in a muffle furnace, cooled naturally to room temperature after annealing, and finally taken out for polishing, and processed into a cladding glass tube matching the above-mentioned core glass rod.

[0029] The core glass rod and the cladding glass tube are combined to obtain an optical fiber preform rod, which is then drawn into an optical fiber using an optical fiber drawing tower to obtain an uncoated optical fiber with a length of 20 m and a diameter of 10 μm.

[0030] The obtained uncoated optical fiber was cut into 10 parts for standby use, each part being 2 m long.

[0031] Example 1

[0032] Take one portion of the uncoated optical fiber prepared in Comparative Example 1, mix bisphenol A epoxy resin and methyl acrylate in a mass ratio of 1:1, evenly coat the mixed material on the optical fiber, cure it under a 460nm light curing lamp for 5 seconds, form a coating layer on the cladding of the uncoated optical fiber, and take it out for use after curing. The structure of the optical fiber obtained in this embodiment is as follows Figure 2 As shown, Figure 2 It is a cross-sectional structure diagram of an optical fiber without a shell on the coating layer; wherein 1 is the core, 2 is the cladding, and 3 is the coating layer.

[0033] Example 2

[0034] Take 1 portion of the spare uncoated optical fiber of Comparative Example 1, mix bisphenol A epoxy resin and methyl acrylate in a mass ratio of 1:2, evenly coat the mixed material on the optical fiber, and cure it under a 460nm light curing lamp for 5 seconds to form a coating layer on the cladding of the uncoated optical fiber. After curing, take it out for use.

[0035] Example 3

[0036] Take 1 portion of the spare uncoated optical fiber of Comparative Example 1, mix bisphenol A epoxy resin and methyl acrylate in a mass ratio of 1:2, add 2wt% of octanoic acid, and evenly coat the mixed material on the optical fiber. Curing it under a 460nm light curing lamp for 2 seconds to form a coating layer on the cladding of the uncoated optical fiber. After curing, take it out for use.

[0037] Example 4

[0038] Take 1 portion of the spare uncoated optical fiber of Comparative Example 1, mix bisphenol A epoxy resin and methyl acrylate in a mass ratio of 1:2, add 2wt% of octanoic acid and 1wt% of cerium oxide, and evenly coat the mixed material on the optical fiber. Curing it under a 460nm light curing lamp for 2 seconds to form a coating layer on the cladding of the uncoated optical fiber. After curing, take it out for use.

[0039] Embodiments 5 to 9

[0040] Take 5 portions of the uncoated optical fiber prepared in Comparative Example 1, of which 1 portion is directly coated with an ABS plastic shell with a mesh metal copper reinforcement as Example 5, and the other 4 portions are coated with an ABS plastic shell with a mesh metal copper reinforcement on the uncoated optical fiber according to the methods of Examples 1 to 4 as Examples 6 to 9. The structures of the optical fibers obtained in Examples 6 to 9 are as follows: Figure 3 As shown, Figure 3 It is a cross-sectional structural diagram of an optical fiber with a shell covering the coating layer; wherein 1 is the core, 2 is the cladding layer, 3 is the coating layer, and 4 is the shell.

[0041] Example 10

[0042] A laser therapy device was used to emit light with a wavelength of 976 nm. The optical fibers prepared in Comparative Example 1 and Examples 1 to 9 were used as test objects. The light intensity attenuation rates of the light with a wavelength of 976 nm were detected after passing through the test objects. The length of the test object was 2 m. The test results are shown in Table 2.

[0043] Table 2

[0044]

[0045]

[0046] Comparison between Example 1 and Comparative Example 1 shows that the performance improvement effect of the modified optical fiber of the present invention is very obvious.

[0047] Comparison between Example 2 and Example 1 shows that increasing the amount of methyl acrylate in the preparation process of the modified optical fiber can improve the light transmission efficiency of the modified optical fiber.

[0048] Comparison between Example 3 and Example 2 shows that the addition of octanoic acid shortens the light curing time without reducing the light transmission efficiency of the optical fiber.

[0049] Comparison between Example 4 and Example 3 shows that the addition of rare earth further improves the light transmission efficiency of the optical fiber.

[0050] Examples 5 to 9 are compared with Comparative Example 1 and Examples 1 to 4, respectively, indicating that the metal-reinforced plastic shell coated on the optical fiber can effectively shield static electricity.

[0051] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. A modified optical fiber, comprising, from the inside to the outside, a glass core, a glass cladding and a coating layer, wherein the coating layer is prepared by curing a photocurable material through light, characterized in that: The photocurable material includes epoxy resin compounds and acrylate compounds; The photocurable material further includes fatty acid compounds; The fatty acid compound is one or more of caprylic acid, caprylic acid or linoleic acid; The photocurable material further includes rare earth, and the rare earth is one or more of erbium oxide, samarium oxide, and cerium oxide; The refractive index of the glass cladding is less than the refractive index of the glass core; Also included is a metal-reinforced plastic shell coated on the coating layer.

2. The modified optical fiber according to claim 1, characterized in that: The epoxy resin compound is one or more of bisphenol A epoxy resin or novolac epoxy resin; The acrylic acid ester compound is one or more of methyl acrylate, ethyl acrylate, 2-methyl methacrylate or 2-ethyl methacrylate.

3. The modified optical fiber according to claim 1, characterized in that: The main components of the glass fiber core include: 20-54wt% SiO2, 10-16wt% Na2O, 5-9wt% K2O, 10-16wt% CaO, 5-9wt% BaO, 10-16wt% ZnO, 5-9wt% B2O3 and 1-5wt% GeO2; The main components of the glass cladding include: 25-55wt% SiO2, 10-16wt% Na2O, 5-9wt% K2O, 10-16wt% CaO, 5-9wt% BaO, 10-16wt% ZnO and 5-9wt% B2O3.

4. The modified optical fiber according to claim 1, characterized in that: The mass ratio of the epoxy resin compound to the acrylate compound is 1:1-3.

5. The modified optical fiber according to claim 1, characterized in that: The metal product is a mesh-shaped metal or a coil-shaped metal.

6. The modified optical fiber according to claim 1, characterized in that: The metal is iron, chromium, nickel, copper, aluminum, gold, silver, platinum or an alloy thereof.

7. A laser therapeutic apparatus, comprising the modified optical fiber according to claim 1.

Citation Information

Patent Citations

  • Curable composition

    JP2007302774A

  • Optical fiber for optical amplification and optical fiber laser

    JP2009188094A

  • Photocurable nanocomposite

    TW201803951A